2021
DOI: 10.4132/jptm.2020.09.28
|View full text |Cite
|
Sign up to set email alerts
|

Causes of necrotic features in fine-needle aspirates from cervical lymph nodes

Abstract: Fine-needle aspiration (FNA) is an excellent, minimally invasive diagnostic technique for evaluating a mass or lesion. In particular, FNA is commonly used for evaluating enlarged lymph nodes (LNs). In many cases, the aspirate can provide conclusive evidence for a diagnosis; sometimes, the cytology reveals only necrosis. Necrosis of LNs is found in various diseases. Malignant neoplasms (including lymphomas and metastatic carcinomas) must first be excluded. In addition, numerous benign conditions, such as tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Therefore, small biopsies such as FNAC or CNB can only present inflammatory cells or limited cellularity. A previous study reviewed cases that revealed necrotic features in FNAC from cervical lymph nodes [ 28 ]. They reviewed 460 patients, and tuberculosis was the most common etiology in the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, small biopsies such as FNAC or CNB can only present inflammatory cells or limited cellularity. A previous study reviewed cases that revealed necrotic features in FNAC from cervical lymph nodes [ 28 ]. They reviewed 460 patients, and tuberculosis was the most common etiology in the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of novel drug discovery programs for anti-leishmanial and anti-trypanosomal compounds is essential [ 145 , 146 ]. The NTD Drug Discovery Booster (DDB) was launched in 2015 to avoid early-stage commercial obstacles between pharmaceutical participants, allowing the DNDi to search millions of unique compounds and use computational methods to refine the search iteratively in the hunt for new treatment leads [ 147 ]. Since its creation in 2015, the NTD-DDB has launched 45 iterations around 22 seed compounds, with 13 hit series released, of which 6 have progressed to in vivo proof-of-concept studies for Chagas disease, leishmaniasis, or both.…”
Section: Drug Discovery Strategies and Insights Into Current Therapeu...mentioning
confidence: 99%
“…Two compounds from one hit series have demonstrated efficacy in a leishmaniasis infection model: one was transitioned into lead optimization and is progressing to the pre-clinical stage. In 2017, more than 20 novel series were identified and are currently being processed [ 147 ].…”
Section: Drug Discovery Strategies and Insights Into Current Therapeu...mentioning
confidence: 99%
“…Caseation necrosis is the hall mark of tuberculosis and is related to delayed hypersensitivity reaction. [ 8 ]…”
Section: Essential Phenomenon In Lnmentioning
confidence: 99%